Relationship between Predictors of Human Resource Development and Social Security for Attaining Bangladesh’s Vision 2030 - Hassan , Shafiqul (Journal of Ecohumanism, 2024)
Bangladesh Economic Review (2023) as an important measure taken by the Bangladeshi government to foster between human resource development (HRD) and social security (SS) towards achieving the Vision 2030 in the country. Nonetheless, there is insufficient research in the recent time that empirically investigated the relationship between various underlining predictors of human resource development and social security in the country. The primary objective of this study is to explore the highlighted predictors of human resource development and social security in Bangladesh. Quantitative research design was used to examine the variables of this research. The population of this study comprised experts in education, digital technology, health, employment, women/children, social welfare, social security. Convenient sampling technique was used to choose 281 respondents. Both validity and reliability of the instrument were established. Questionnaire was the instrument used for data collection and Statistical Package for Social Science (SPSS) version 23.0 was utilized for data. Descriptive Statistics with frequencies and percentages were used to analyze demographic information of the respondents and Pearson moment product correlation was employed to determine the relation between predictors of predictors of human resource development and social security in Bangladesh. The results of shared variance from Pearson moment product correlation demonstrated that there was high level of correlation between health as a predictor of human resource development and social security; there were moderate correlations between education, digital technology and women/children as predictors of HRD and social security and there were low correlations between social welfare and employment as predictors of HRD and social security in the country.